1973
DOI: 10.2337/diab.22.9.694
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone Secretion after Double Stimulation with Arginine in Normal and Insulin-dependent Diabetic Women

Abstract: The standard intravenous arginine test was modified by infusing two equal doses of arginine eighty minutes apart. The serum growth hormone, blood glucose and plasma free fatty acid responses were studied in fifteen young juvenileonset diabetic women and in seven healthy women of comparable age and weight. The biphasic growth hormone response to the two arginine infusions observed in normals did not occur in the diabetics. In addition, the diabetics differed from the normals in several qualitative aspects of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The same phenomenon was found by Koncz et al (18) after double stimulation with arginine in insulin-dependent diabetic women. This suggests that some cellular inability to react to a normal glucose load is present in the diabetics: whether this is the consequence of the shortage of insulin or results from a receptor cell disease is not clear.…”
Section: Discussionsupporting
confidence: 74%
“…The same phenomenon was found by Koncz et al (18) after double stimulation with arginine in insulin-dependent diabetic women. This suggests that some cellular inability to react to a normal glucose load is present in the diabetics: whether this is the consequence of the shortage of insulin or results from a receptor cell disease is not clear.…”
Section: Discussionsupporting
confidence: 74%
“…The presence of hypercortisolemia prevented neither the decrease of plasma glucose values nor the GH discharge from the pituitary gland despite the known action of glucocorticoids to increase glucose production via gluconeogenesis and cause resistance to insulin action [5]. Whereas others have not found arginine infusion to be a consistent stimulus for GH secretion in monkeys [6], our data show that the infusion causes a consistent release, in fact, similar to that observed in man [9, 11, 20]. It is likely that procedural differences account for this discrepancy.…”
Section: Discussionmentioning
confidence: 47%
“…Most studies used infusion type supplements; however, four studies assessed the effect of oral supplements [ 6 , 28 , 33 , 34 , 36 ]. Twenty-one studies assessed the response of GH to ARG alone [ 6 , 8 , 11 13 , 28 30 , 32 , 34 , 36 , 38 , 44 , 50 , 53 55 , 62 , 63 , 65 , 66 ], and twenty-one studies investigated the response of GH to ARG + GHRH [ 6 , 8 , 31 , 33 , 35 , 37 , 40 43 , 47 49 , 52 , 56 59 , 61 , 67 , 68 ]. Some studies demonstrated the responsiveness of GH to combinations of ARG with other amino acids like lysine and ornithine [ 30 , 39 ].…”
Section: Resultsmentioning
confidence: 99%